Disharmony of Regulation in the Social Function of Islamic Banking in Indonesia - Pratami, Aisyah Kansa; Tajrid, Amir; Rifqi, Lathif Hanafir (Al-Hurriyah: Jurnal Hukum Islam, 2025)
Islamic banking regulations in Indonesia have so far displayed a paradox between positive legal legitimacy and the ideals of sharia maqashid. This study examines the disharmony between positive regulation of Islamic banking and the principle of sharia maqashid in the implementation of the social function of Islamic banks in Indonesia. This study is motivated by the phenomenon of policy orientation that emphasizes administrative compliance and financial stability, while the aspects of equity and distributive justice receive less normative space. Using a historical-juridical approach and normative-interpretive analysis, this study examines the synchronization between Law No. 21 of 2008, OJK regulations, and Bank Indonesia's policies with sharia maqashid values. The results of the study show that the existing regulatory framework is not fully maqashid-compatible because it is still technocratically oriented and has not measured the social impact substantively. This study recommends the reconstruction of social function regulations based on the principles of maqashid compliance, the integration of social justice indicators into supervision instruments, and the strengthening of maqashid literacy as the foundation for the renewal of national sharia economic law.